The Influence of Customer Expectation and Marketing Mix on Customer Loyalty with Customer Satisfaction as Intervening - Mukarromah, Syarifatul; Hardyanto, Wahyu; Eko Pramono, Suwito (Educational Management, 2021)
The purpose of this study was to determine whether there is an effect of customer expectations and marketing mix on customer loyalty with customer satisfaction as an intervention at SMK Al-Ittihad. All activities carried out by a school will ultimately lead to students' value regarding their perceived satisfaction. If student satisfaction is realized, loyalty to school is also manifested. This study's population were all SMK Al-Ittihad Boarding School Jungpasir, Wedung, Demak in the 2020/2021 academic year, with the sampling technique being the Stratified Random Sampling technique. The data collection technique is a questionnaire. The path analysis results (Path Analysis) show that there is a significant influence between the variable Customer Expectations and the Marketing Mix partially on Customer Satisfaction with the Sig. <0.05. Directly there is a significant influence between the variable Customer Expectations and Customer Satisfaction with Customer Loyalty with the Sig Value. <0.05, and there is no significant influence between the Marketing Mix variable and Customer Loyalty with the Sig. 0.778> 0.05. Customer Expectations directly affect Customer Loyalty with the direct effect value is greater than the indirect effect value (0.507> 0.316). Marketing Mix directly affects Customer Loyalty with the greater direct effect value than the indirect effect value (0.013> -0.201). This research is useful as input in the development of management science, especially in marketing management.